Complement receptor CD46 co-stimulates optimal human CD8+ T cell effector function via fatty acid metabolism - Giuseppina Arbore (Nature Portfolio, 2018)
Complement, while serving to remove pathogens in the circulation, is also important for synergizing with inflammasomes to modulate CD4 T cell activation. Here the authors show that CD46, a complement receptor expressed only in humans, is essential for inducing optimal activation and effector functions of human CD8 T cells.